The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1177/0192623311406933
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Toxicity Study of ST-20 (NSC-741804) by Oral Gavage in Sprague-Dawley Rats

Abstract: ST-20 (sodium 2,2-dimethylbutyrate) is a potential therapeutic agent for treatment of b-thalassemia and sickle cell disease. A subchronic oral toxicity study was conducted in Sprague-Dawley rats (10/sex/dose) at gavage dosages of 0 (vehicle control), 200, 600, or 1,000 mg/kg, once daily for up to 15 days followed by a 14-day recovery. Ataxia (females), rough coat/thin appearance (males), and decreased body weights were observed at 1,000 mg/kg. Functional observational battery (FOB) deficits were observed more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Based on the absence of adverse effects, the NOAEL for HST5040A was 300 mg/kg/day, the highest dose level tested, which provided exposures well above those projected to occur at the clinical efficacious dose. Overall, these data are similar to previously reported preclinical safety data with this molecule. , Based on these data and the pharmacological activity in disease models, HST5040 was selected as a clinical development candidate for the treatment of PM and MMA.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Based on the absence of adverse effects, the NOAEL for HST5040A was 300 mg/kg/day, the highest dose level tested, which provided exposures well above those projected to occur at the clinical efficacious dose. Overall, these data are similar to previously reported preclinical safety data with this molecule. , Based on these data and the pharmacological activity in disease models, HST5040 was selected as a clinical development candidate for the treatment of PM and MMA.…”
Section: Discussionsupporting
confidence: 83%
“…Overall, these data are similar to previously reported preclinical safety data with this molecule. 31,32 Based on these data and the pharmacological activity in disease models, HST5040 was selected as a clinical development candidate for the treatment of PM and MMA.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…In contrary to the previous studies, our findings demonstrated that administration of SB alone has altered bone marrow erythropoiesis based on the marked increase of PCEs percent in the bone marrow (3.39 ± 0.05 * ), that may be attributed to the increased ratio of the antiapoptotic proteins BCL-XL and MCL-1 to their proapoptotic partners BCL-XS and MCL-1SL, respectively, as demonstrated by Castaneda et al (2005), who found that SB induces erythroid cell progenitor survival and proliferation in vitro through BCLfamily antiapoptotic protein expression (Castaneda et al 2005). On the other hand, Terse et al showed that SB did not significantly change PCEs percentage, indicating that it did not change bone marrow erythropoiesis at the tested doses (6.25 and 12.5 mM) (Terse et al 2011). Anyway, the underlying mechanism of the observed hematologic effects at the dose tested is not completely understood.…”
Section: Discussionmentioning
confidence: 89%
“…A broad review of the literature suggested that clinical pathology is most often incorporated in the recovery groups to evaluate reversibility of organ dysfunction (such as renal, hematopoietic, immune, and endocrine systems), with fewer reports incorporating clinical pathology to monitor tissue injury (Abraham, Gottschalk, and Ungemach 2005;Boorman et al 1982;Henzen et al 2000;Derelanko et al 1985;Lefebvre et al 1984;Rouse et al 2011;Streck and Lockwood 1979;Terse et al 2011).…”
Section: Current Pharmaceutical Practicesmentioning
confidence: 99%
“…A large global retrospective analysis detailing general practices for use of recovery groups (Sewell et al 2014) provided recommendations for minimizing recovery animals where scientifically justified, including avoiding recovery phases in first in human (FIH)-enabling studies. A broad review of the literature suggested that clinical pathology is most often incorporated in the recovery groups to evaluate reversibility of organ dysfunction (such as renal, hematopoietic, immune, and endocrine systems), with fewer reports incorporating clinical pathology to monitor tissue injury (Abraham, Gottschalk, and Ungemach 2005;Boorman et al 1982;Henzen et al 2000;Derelanko et al 1985;Lefebvre et al 1984;Rouse et al 2011;Streck and Lockwood 1979;Terse et al 2011).…”
Section: Current Pharmaceutical Practicesmentioning
confidence: 99%